2009
DOI: 10.1055/s-0028-1098843
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Criteria for the Confirmation of Implant Rotation and the Development of an Implant-Capsule-Interaction (“Interface”) in Anatomically Formed Textured Breast Implants with Texturised Biocell®-Surface

Abstract: !

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…Numerous factors influence implant rotation [12]. A lack of connective tissue adhesion between the implant and the capsule can occur, prompting movement of the implant in the pocket [5]. Heitmann et al [13], in their report, found that six of 132 patients experienced implant rotation because the surgical pocket was too large.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors influence implant rotation [12]. A lack of connective tissue adhesion between the implant and the capsule can occur, prompting movement of the implant in the pocket [5]. Heitmann et al [13], in their report, found that six of 132 patients experienced implant rotation because the surgical pocket was too large.…”
Section: Introductionmentioning
confidence: 99%
“…Los implantes de gel cohesivo, por ser más rígidos, mantienen su forma y rotan menos (13). Se han descrito técnicas quirúrgicas, como colocar el polo superior o la mitad superior del implante debajo de la fascia superficial del músculo pectoral mayor en vez de subpectoral o retroglandular, para minimizar esta complicación (14).…”
Section: Hallazgos Ecográficos Asociados a Complicaciones De Los Implantes Mamariosunclassified
“…Los marcadores en la superficie anterior del implante en el polo inferior están hechos para el monitoreo intraoperatorio por palpación, para asegurar una posición adecuada (14). Cuando un implante es redondo y se rota, por su forma más simétrica, no cambia mucho su apariencia clínica, pero un implante anatómico sí varía clínicamente al rotar y parece deformado (11,13).…”
Section: Hallazgos Ecográficos Asociados a Complicaciones De Los Implantes Mamariosunclassified
See 2 more Smart Citations